Photocatalytic performance of CuO NPs: An experimental approach for process parameter optimization for Rh B dye - Hridoy Saha; Ankita Dastider; Md Jannatul Ferdous Anik; Samiya Rahman Mim; Sovendo Talapatra; Utsha Das; Moniruzzaman Jamal; Md Muktadir Billah (Results in Materials)
Optimization of process parameters for photocatalytic activity measurement of CuO nanoparticles (NPs) was the focus of this study. CuO NPs were prepared following chemical co-precipitation method and characterized using X-ray diffraction (XRD), ultraviolet visible (UV–vis) spectroscopy, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) and Fourier transform infrared spectroscopy (FTIR). Subsequent studies concentrated on optimizing pH of Rhodamine B (Rh B) dye, catalyst doses, and concentration of hydrogen peroxide (H2O2) for effective photocatalytic degradation. This optimization process was intended to properly investigate the photocatalytic activity of CuO NPs using Rh B dye (5 ppm), a frequently encountered organic pollutant. After 180 min of UV irradiation at optimized condition (pH 10, 0.3125 mg/mL NPs, 9000 ppm H2O2) a degradation rate of 60 percent was recorded. These findings maximized the degradation efficiency of CuO NPs to exploit as a potential photocatalyst.